Profil Kemandirian Belajar Siswa SD Pada Pembelejaran Matematika Di Masa Pandemi Covid-19 - febriyanti ayu nurmala sari; Arrisona Dia Indah sari; Afakhrul Masub Bachtiar (IJPSE : Indonesian Journal of Primary Science Education, 2023)
Look at the current state of learning. Several problems were found, which can be seen from theway students learn which is very diverse. There are active and passive students. There are studentswho are independent and some are dependent on others. In this study, the researcher will describethe learning independence of students at SD Muhammadiyah Sidayu, where a sample of studentswith high, medium and low learning independence is taken from the questionnaire given alongwith consultation with the teacher, after the sample is taken the researcher conducts interviewswith the homeroom teacher and homeroom teacher after that compare transcript of daily gradesand final semester grades. The results obtained by students who are highly independent have fewobstacles in their learning and are able to solve them on their own. Meanwhile, students with lowindependence find it difficult to solve their learning problems. The level of learning independencealso affects the value obtained. Students who have high learning independence get scores abovethe average of their classmates. Vice versa, students who have low learning independence getscores below the average of their classmates.